Best practice in DAM implementations - Wadey, Alec (Henry Stewart Talks, 2010)
Digital Asset Management, DAM Implementation, Systems Integration, Enterprise DAM Environments, SaaS DAM Environments, DAM Infrastructure, DAM Technology, Metadata Management, Taxonomy Management, DAM Workshops, Cloud Computing